Prevalence and Assessment of Periapical Lesions in Subjects Reporting to a Private Teaching Hospital, Chennai,India : A Retrospective Study - Chris Noel Timothy1, Pratibha Ramani (Indian Journal of Forensic Medicine & Toxicology, 2020)
Apical or periapical lesions are inflammatory processes which are generally caused by microorganisms ortheir by-products and manifest due to defense response of the host to the stimulus in the root canal system.The aim of this study was to assess prevalence of periapical lesions among the south indian population.This was a descriptive study, where the data of the patients who reported to the dental clinics in saveethadental college, SIMATS, Chennai, India, was obtained from the department of conservative dentistryand endodontics. Data was further analyzed, recorded in microsoft excel software and was subjected tostatistical analysis. n = 15 for periapical lesions. From the data analysed through SPSS, it is observed thatthe prevalence of periapical lesions among non - vital teeth among the outpatients in the department oforal pathology is 1.1%. The age group of 60 - 70 years was the most commonly observed (60%). Malepredilection was noted (67%). Radiographic examination was performed for 40% and histopathologicalexamination was performed for 6.7% of the teeth with periapical lesions. 100% of the teeth observed inthe current study were non - vital. Periapical abscess was the most common finding (53.3%). Occurringmostly in anterior maxillary, anterior mandibular and posterior mandibular regions (26.7%) each. The mostcommonly observed treatment modality was extraction (73.7%). Within the limitations of the current study ,there exists increased prevalence of periapical pathology above 60 years, predominantly in the age group of60 - 70 years, primarily reported in the undergraduate clinics. Routine dental checkup with both radiographicand histopathological examination of the periapical lesions is essential for the survival of the tooth and isbeneficial for the community.